2010
DOI: 10.5142/jgr.2010.34.4.342
|View full text |Cite
|
Sign up to set email alerts
|

Ginseng for Reducing the Blood Pressure in Patients with Hypertension: A Systematic Review and Meta-Analysis

Abstract: Ginseng is one of the most-widely used herbal remedies. This systematic review evaluates the current evidence for its use in the reducing blood pressure (BP) in patients with hypertension. Systematic searches of 12 electronic databases were conducted without language restrictions. All randomized clinical trials (RCTs) of ginseng as a treatment for hypertension were candidates for inclusion. Methodological quality was assessed using the Cochrane risk of bias. Five RCTs met the inclusion criteria. The risk of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 20 publications
1
14
0
1
Order By: Relevance
“…Total saponins and Rg3 are also involved in vasodilation; the mechanism is associated with the release of NO and the activation of Ca 2+ -dependent K + channels in vascular smooth muscles [20]. Previous studies have demonstrated that an 8–9% decrease in blood pressure may induce a 21% decrease in heart attacks, as well as a 37% reduction in stroke [21]. In the present study, HCEF-RG of 1,000 mg/kg was administered to SHR, which is equivalent to a daily Rg3 intake of 4.04 mg. After 8 wk of treatment, a 17% decrease in systolic blood pressure, as well as an 11% reduction in diastolic blood pressure was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Total saponins and Rg3 are also involved in vasodilation; the mechanism is associated with the release of NO and the activation of Ca 2+ -dependent K + channels in vascular smooth muscles [20]. Previous studies have demonstrated that an 8–9% decrease in blood pressure may induce a 21% decrease in heart attacks, as well as a 37% reduction in stroke [21]. In the present study, HCEF-RG of 1,000 mg/kg was administered to SHR, which is equivalent to a daily Rg3 intake of 4.04 mg. After 8 wk of treatment, a 17% decrease in systolic blood pressure, as well as an 11% reduction in diastolic blood pressure was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Five of them include studies published in English only [10][12], [16], two analysed the results from English and Chinese databases [8], [9], and the other five searched several available databases, including Korean, Chinese, English and Japanese databases [1], [3], [6], [13], [14]. However, these reviews failed to include several recent studies published in Korea, where the name panax ginseng is from.…”
Section: Introductionmentioning
confidence: 99%
“…Another study suggested that red ginseng (RG) extended the duration of tolerance to cold stress [16]. However, ginseng is generally known to alleviate heat-related symptoms, including xerostomia and hypertension, in addition to cold-related symptoms [8,17]. Therefore, in this study we examined its effects on heat-related symptoms, as well as cold-related symptoms.…”
Section: Discussionmentioning
confidence: 95%